2019
DOI: 10.1016/j.critrevonc.2019.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Effects of current parenteral nutrition treatment on health-related quality of life, physical function, nutritional status, survival and adverse events exclusively in patients with advanced cancer: A systematic literature review

Abstract: Background:The aim was to evaluate the effects of current parenteral nutrition (PN) treatment on clinical outcomes in patients with advanced cancer. Methods:This review was conducted according to the PRISMA guidelines (PROSPERO ID: 4201707915).Results: Two underpowered randomized controlled trials and six observational studies were retrieved (n=894 patients). Health-related quality of life and physical function may improve during anti-neoplastic treatment in who PN treatment is the only feeding opportunity, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(29 citation statements)
references
References 32 publications
(188 reference statements)
0
29
0
Order By: Relevance
“… 67 Another systematic review found that PN in patients with advanced cancer was understudied and that the level of evidence was weak. 68 The PS and Glasgow Prognostic Score impact strongly on survival in patients with advanced cancer receiving home PN. 69 From this, it has been suggested that PN should be avoided if the ECOG/WHO PS is 3 or 4.…”
Section: Nutritional Interventionsmentioning
confidence: 99%
“… 67 Another systematic review found that PN in patients with advanced cancer was understudied and that the level of evidence was weak. 68 The PS and Glasgow Prognostic Score impact strongly on survival in patients with advanced cancer receiving home PN. 69 From this, it has been suggested that PN should be avoided if the ECOG/WHO PS is 3 or 4.…”
Section: Nutritional Interventionsmentioning
confidence: 99%
“…A qualitative study among patients with cancer with CIF showed they had a favorable perception of the impact of PN [7]. Previous studies assessing QoL with validated tools were longitudinal, without randomization, entailing a major risk of bias, as QoL improvements could result from the efficacy of anticancer treatments [8][9][10][11][12]. There is another randomized study that was similar to ours, in the sense that the population included patients with advanced cancer with a functional digestive tract receiving PN.…”
mentioning
confidence: 61%
“…Thus, it i show artificial nutritional support provides the nutritional elements fundamental to recover strength and movement. Tobberup et al,( 20 ) found in a systematic review and meta-analyses, a prospective randomized controlled study that evidenced positive changes in physical performance in the six-minute walk test in patients assigned randomly to receive parenteral nutrition.…”
Section: Discussionmentioning
confidence: 99%